Perseus arm – a new perspective on star formation and spiral structure in our home galaxy. Issue 1 (29th September 2021) - Wienen, M; Brunt, C M; Dobbs, C L; Colombo, D
ABSTRACT: Expansion of (sub)millimetre capabilities to high angular resolution offered with interferometers allows to resolve giant molecular clouds (GMCs) in nearby galaxies. This enables us to place the Milky Way in the context of other galaxies to advance our understanding of star formation in our own Galaxy. We, thus, remap 12 CO (1–0) data along the Perseus spiral arm in the outer Milky Way to a fixed physical resolution and present the first spiral arm data cube at a common distance as it would be seen by an observer outside the Milky Way. To achieve this goal, we calibrated the longitude–velocity structure of 12 CO gas of the outer Perseus arm based on trigonometric distances and maser velocities provided by the BeSSeL survey. The molecular gas data were convolved to the same spatial resolution along the whole spiral arm and regridded on to a linear scale map with the coordinate system transformed to the spiral arm reference frame. We determined the width of the Perseus spiral arm to be 7.8 ± 0.2 km s −1 around the kinematic arm centre. To study the large-scale structure, we derived the 12 CO gas mass surface density distribution of velocities, shifted to the kinematic arm centre, and arm length. This yields a variation of the gas mass surface density along the arm length and a compression of molecular gas mass at linear scale. We determined a thickness of ∼63 pc on average for the Perseus spiral arm and a centroid of the molecular layer of 8.7 pc.